1997
DOI: 10.1103/physrevlett.79.2269
|View full text |Cite
|
Sign up to set email alerts
|

Positron-Annihilation Study of Icosahedral AlPdMn Alloys

Abstract: polyquasicrystalline icosahedral quasicrystals. As-grown and plastically deformed single quasicrystals of Al 70.6 Pd 21.1 Mn 8.3 were also studied. In every sample the lifetime spectrum consists of a single component with the lifetime of 206 6 4 ps. The results indicate that icosahedral quasicrystalline AlPdMn contains a dense distribution of vacancy-type sites. These trapping sites seem to remain unaltered during plastic deformation at high temperature. [S0031-9007 (97)04002-7]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…We sug- gest another mechanism responsible for the roughening procedure. It is well known that quasicrystals contain many vacancies the total concentration of which can exceed 10% as has been studied by positron lifetime investigations, for instance [8,14]. It is reasonable to assume that upon heating the vacancies assemble to form voids that requires heterogeneous nucleation, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We sug- gest another mechanism responsible for the roughening procedure. It is well known that quasicrystals contain many vacancies the total concentration of which can exceed 10% as has been studied by positron lifetime investigations, for instance [8,14]. It is reasonable to assume that upon heating the vacancies assemble to form voids that requires heterogeneous nucleation, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it seems reasonable to consider that the structures in some icosahedral and decagonal phases can also be regarded as modulated structures due to CDWs; the formation and stability of these phases are related to the valence electron concentration (Tsai et al, 1990(Tsai et al, , 1994. Positron annihilation measurements showed that a high density of atomic vacancies exists in icosahedral phases (Kanazawa et al, 1997). Moreover, it should be noted that the structure of/tAI4Mn (Shoemaker et al, 1989), which is closely related to the icosahedral and decagonal phases, is composed of layers with ordered atomic vacancies.…”
Section: Journal Of Applied Crystallographymentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Most investigations of defects in quasicrystals focused on line or planar defects, 8,9 which give rise to clear contrasts in transmissionelectron microscope images, or on phason strain fields, whose signatures can be observed by neutron-and x-ray scattering experiments. 10 Point defects, such as vacancies, turned out to be much more difficult to identify and characterize, because positron annihilation measurements [11][12][13] could not distinguish between missing atoms, i.e., real vacancies, and the densely distributed vacancylike sites arising from open spaces in, e.g., the perfect Al-Pd-Mn quasicrystal structure. 11,12 The high concentration of open spaces in the perfect icosahedral structure makes all positrons annihilate in such open spaces, which have long positron lifetimes and thus appear as vacancylike sites.…”
Section: Introductionmentioning
confidence: 99%
“…10 Point defects, such as vacancies, turned out to be much more difficult to identify and characterize, because positron annihilation measurements [11][12][13] could not distinguish between missing atoms, i.e., real vacancies, and the densely distributed vacancylike sites arising from open spaces in, e.g., the perfect Al-Pd-Mn quasicrystal structure. 11,12 The high concentration of open spaces in the perfect icosahedral structure makes all positrons annihilate in such open spaces, which have long positron lifetimes and thus appear as vacancylike sites. As a consequence the positron annihilation signals are saturated and no decomposition of the lifetime spectra is possible.…”
Section: Introductionmentioning
confidence: 99%